The definitive guide to HR communication : engaging employees in benefits, pay, and performance - Davis, Alison (Alison Bonnie), 1957-; Shannon, Jane, 1943- (Upper Saddle River : FT Press)
Includes bibliographical references (p. 279-280) and index